Addressing urban disorder without police: How Seattle's LEAD program responds to behavioral‐health‐related disruptions, resolves business complaints, and reconfigures the field of public safety. (12th December 2021) - Stuart, Forrest; Beckett, Katherine
Abstract: Since the late twentieth century, as part of a broad effort to maximize the profitability of commercial spaces and address the complaints of business interests, cities have increasingly criminalized the presence and behavior of populations perceived as disorderly. The resulting police interactions produce a range of deleterious outcomes, particularly for individuals contending with mental health and substance use disorders, homelessness, and other behavioral health concerns. Against this backdrop, we provide a case study of Let Everyone Advance with Dignity (LEAD), a novel public safety intervention developed in Seattle, Washington. LEAD diverts businesses' disorder complaints from police and 911 toward program personnel who provide long‐term harm reduction services and resources. LEAD's non‐punitive approach has demonstrated success in reducing the harms of criminalization, improving individual outcomes, satisfying business grievances, and, more broadly, disrupting the defining logic and practices of neoliberal urbanism. LEAD's successes carry theoretical implications, demonstrating the need for nonpolice alternatives to reconfigure the organizational field of public safety by intervening into the longstanding coalition between businesses and police. The LEAD model also offers insights about the concrete steps necessary to ensure public safety and community vitality without police involvement.